Throughout Pathological Study on Skin, Subcutaneous and Mucosal Neoplasia of the Dromedary Camel - Sobayil , Fahd A.; El-Amir, Yasmin O. (Brazilian Journal of Veterinary Pathology, 2013)
The aim of this study was to record, classify and describe some external tumors of single-humped camels as well as their diagnosis after surgical excision and to determine the link between occurrence of tumors and breed, sex, age, coat color, and tumor location. Clinical cases of tumors (n =26) were presented for surgical treatment. Camels were subjected to detailed study including breed, age, sex, and coat color of the animal, case history, gross and microscopic appearance of the tumor, surgical treatment, and postoperative care. This study showed that tumors were seen in three local breeds: Maghateer (n=13), Majaheem (n=12), and Sofr (n=1). Four different types of tumors were diagnosed in camels, namely, squamous cell carcinoma (SCC), fibroma, lipoma and fibromyxosarcoma. The most common type of tumor in Maghateer breed which have white colored coat was SCC (69.2%), while in Majaheem breed which have dark brown to black coat was fibroma (66.7%). Incidence of neoplasia was significantly higher in females than males. The age of the animals had no significant effect either on the site or type of tumor.